Identifying Nutrient Deficiencies in Ornamental Plants - Amy L. Shober; Geoffrey C. Denny (EDIS)
SL318, a 4-page illustrated fact sheet by Amy L. Shober and Geoffrey C. Denny, provides guidance for the visual diagnosis of major nutrient deficiency symptoms in ornamental plants. Published by the UF Department of Soil and Water Science, March 2010.